Dimensions of dynamic marketing capability and export performance. Issue 5 (26th October 2020) - Hoque, Mohammad Tayeenul; Ahammad, Mohammad Faisal; Tzokas, Nikolaos; Gabay, Gillie
Abstract : Purpose: The purpose of this paper is to develop a conceptual framework on the dimensions of dynamic marketing capability (DMC) and its relationship with export performance. The paper also proposes the mediating role of competitive hybrid strategy and the moderating role of environmental responsiveness in explaining the relationship between DMC and export performance. Design/methodology/approach: By following the dynamic capability notion of the marketing and competitive strategy literature, this paper proposes a novel conceptualization of the DMC development process and the possible effect of DMC on attaining competitive advantage. Findings: The paper postulates that a firm's DMC can reflect complementary power when its higher-level marketing capabilities are bundled together to detect distributing channel members' crucial needs, competitors' action plans and satisfying market demand. As yet little is known about the main underlying dimensions of higher-level DMC construct, the paper contributes in proposing the key dimensions of DMC. Originality/value: This research advances the knowledge-based view and resource-based views and evolves a solid foundation of DMC constructs comprising four higher-order marketing capabilities, namely, ambidextrous market orientation, customer relationship management capability, brand management capability and new product development capability. Thus, this paper contributes in DMC literature in explaining export performance.